Learner Choice, Learner Voice A Teacher's Guide to Promoting Agency in the Classroom. - Schaaf, Ryan L.; Zayas, Becky; Jukes, Ian. (Milton : Eye On Education, Incorporated, 2022)
Learner Choice, Learner Voice offers fresh, forward-thinking supports for teachers creating an empowered, student-centered classroom. Learner agency is a major topic in today's schools, but what does it mean in practice, and how do these practices give students skills and opportunities they will need to thrive as citizens, parents, and workers in our ever-shifting climate? Showcasing authentic activities and classrooms, this book is full of diverse instructional experiences that will motivate your students to take an agile, adaptable role in their own learning. This wealth of pedagogical ideas - from specific to open-ended, low-tech to digital, self-expressive to collaborative, creative to critical - will help you discover the transformative effects of providing students with ownership, agency, and choice in their learning journeys.
Description based upon print version of record.
Keywords: Teaching; Student-centered learning; EDUCATION / Classroom Management; EDUCATION / Educational Psychology